2006
DOI: 10.3233/jad-2006-9211
|View full text |Cite
|
Sign up to set email alerts
|

Peri-nuclear clustering of mitochondria is triggered during aluminum maltolate induced apoptosis

Abstract: Synapse loss and neuronal death are key features of Alzheimer's disease pathology. Disrupted axonal transport of mitochondria is a potential mechanism that could contribute to both. As the major producer of ATP in the cell, transport of mitochondria to the synapse is required for synapse maintenance. However, mitochondria also play an important role in the regulation of apoptosis. Investigation of aluminum (Al) maltolate induced apoptosis in human NT2 cells led us to explore the relationship between apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Several lines of evidence suggest that apoptosis is the major mode of cell death induced by Al [12], [13]. A study by [14] indicated association of Al induced apoptosis with potential role of p53 signaling in Neuro 2a cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that apoptosis is the major mode of cell death induced by Al [12], [13]. A study by [14] indicated association of Al induced apoptosis with potential role of p53 signaling in Neuro 2a cells.…”
Section: Introductionmentioning
confidence: 99%
“…The medical importance of understanding vesicle-transporting motors is highlighted by several recent studies, which describe the potential role of axonal transport deficiencies in neurodegenerative conditions such as Alzheimer's disease [10][11][12]. Previously, the overexpression of the microtubule associated protein tau was shown to inhibit kinesin dependent transport [13].…”
Section: Introductionmentioning
confidence: 99%
“…These events suggest that Al targets mitochondrial mediated apoptosis pathway and mitochondrial changes, following cytotoxic stimuli representing a primary event in apoptotic cell death. Al maltolate induced apoptosis in human NT2 cells via disruption of mitochondrial transport of NT2 cells that exhibited peri-nuclear clustering of mitochondria [43].…”
Section: Discussionmentioning
confidence: 99%